(untitled) (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: The housing system is a crucial determinant of animal welfare. This study aimed to compare the effects of intensive housing with those of alternative floor housing on the welfare of rabbits and their meat production. Materials and Methods: Eighty New Zealand rabbits (40 females and 40 males) with an initial mean weight of 1.3 kg and aged 35 days were distributed into four treatment groups. Treatment 1 (T1) comprised five floor cages with four male rabbits in each cage; Treatment 2 (T2) comprised five floor cages, each containing four female rabbits; Treatment 3 (T3) consisted of five elevated cages housing four male rabbits each, and Treatment 4 (T4) consisted of five elevated cages housing four female rabbits each. Indicators of carcass quality, including moisture, protein, lipids, ash, pH, color (L*, a*, b*), physiological stress (plasma cortisol), oxidative stress (lipid oxidation TBARS), and number of antioxidants (FRAP) in the plasma and tissue, were measured. Results: A significant difference (p < 0.05) in pH was observed between the conventional cages and the floor cages, as well as in cortisol levels for the traditional and floor cages (p < 0.05), respectively. Additionally, lipid oxidation (TBARS) was not significantly different in plasma but was significantly different in meat. The TBARS value was higher for floor cages and lower for conventional cages. The FRAP value was not significantly different between plasma and meat (p < 0.05). The findings demonstrate that the use of floor cages does not affect the nutritive value of rabbit meat. Conclusion: The type of cage used affects rabbits’ physiological stress levels and lipid oxidation in muscle tissue, which impacts meat quality. The nutritional value of meat remains unaffected, regardless of the cage type or sex of the rabbit. The floor cage environment enables the rabbits to engage in activities typical of their species, thereby contributing to the animals’ welfare by improving driving skills, attitudes, and handler behavior. J. Adv. Vet. Anim. Res., 12(4): 1237–1242, December 2025 http://doi.org/10.5455/javar.2025.l984